Buddhist Revitalization and Chinese Religions in Malaysia - Tan, Lee (Religion and Society in Asia, 2021)
Frontmatter -- Religion and Society in Asia -- Table of Contents -- Abbreviations -- List of Chinese Characters -- Orthography -- 1 Introduction -- 2 A Brief History of Buddhist Transnational Connections Abstract -- 3 Reforming Chinese Buddhism through the Zheng Xin (Right Faith) Movement -- 4 New Transnational Connections with Taiwan -- 5 Remaking Chinese Buddhists -- 6 Counterforces of Buddhist Revitalization -- 7 Conclusion -- Appendices -- Bibliography -- Index